Implementasi Penerimaan Rutin Muqoddaman dalam Meningkatkan Kualitas Membaca Al-Qur'an di Greges, Donotirto, Kretek, Bantul - Anang Fahrudin; Aida Hayani (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
Recitation is one of the activities concerning learning the Islamic religion usually in society led by someone who is experienced in his field, can be a teacher of the Koran or a preacher to the congregation (mad'u). The Muqoddaman Routine Recitation is held in Greges Hamlet, Donotirto, Kretek, Bantul. One thing that is unique is that now it is entering modern times, but in Greges Hamlet it still maintains many series of religious activities, one of which is the Muqoddaman Routine Recitation which has been going on for sixteen years. The purpose of this research is to find out how it is held, how the impact is generated by this event, and what are the factors that support and hinder the implementation of this Muqoddaman Routine Recitation. The results of this study are 1). The Muqoddaman Routine Recitation is held once every 35 days on Legi Sunday (Javanese market) and starts after the evening prayer until 20.00 WIB. The agenda for this activity is the opening, Tawasul, recitation of the 30 chapters of the Qur'an, prayer, prayer, rest and finally the study of Qur'an Interpretation. 2). The impact resulting from the Muqoddaman Routine Recitation is the creation of generations and Qur'anic people who like to read the Qur'an. Improving the quality of reading and fluency in reading the Qur'an. Increased knowledge and insight from the results of participating in the study of Qur'an Interpretation. 3). Then the factor that supported the implementation of the Muqoddaman Routine Recitation was the support of the entire GregesHamlet community who always made religious activities successful by joining this assembly. In addition, material support was also provided from the community for this assembly. While the inhibiting factors for the MuqoddamanRoutine Recitation are natural factors such as heavy rain accompanied by strong winds, flooding and rotating power outages. Keywords: Implementation, Recitation, Muqoddaman, Quality of Reading, Al-Qur'an